Frequency-Selective Feeding Network for Concurrent Multi-Frequency Wireless Systems Using Enhanced Multi-Stub Line Matching Topology - Jeonghyo Lee; Dongseop Lee; Myoungsun Kim; Wonjeong Jo; Sungjun Han; Wonbin Hong (IEEE Access, 2025)
This paper introduces a new approach to developing a compact dual-wideband feeding network designed to support simultaneous operation across distinct frequency bands, addressing the evolving demands of modern wireless communication and sensing systems. The proposed feeding network, termed the Compact, Low-Loss, Selective Coupler (CLSC), enhances isolation levels and transmission efficiency while maintaining a highly integrated structure. The CLSC concept is demonstrated at 24-30 GHz and 39-50 GHz, utilizing a multi-stub line matching topology, with scalability to other frequency ranges. In the designated dual-frequency bands, the optimized CLSC achieves exceptionally low insertion loss, with transmission coefficients near −1.5 dB, ensuring efficient power distribution. Simultaneously, it maintains an isolation level exceeding −20 dB across the blocked frequency bands, with peak isolation reaching −70 dB—a level unparalleled in conventional feeding networks. These results highlight the capability of the CLSC to precisely filter and manage multiple frequency bands, making it a highly promising solution for next-generation phased arrays, millimeter-wave communication, and advanced antenna systems.